2021
DOI: 10.1007/s11804-021-00217-y
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Solid Oxide Fuel Cell Plant on Board a Cruise Ship

Abstract: The work is a case study of a cruise ship supplied by liquefied natural gas (LNG) and equipped with a solid oxide fuel cell (SOFC). It is supposed that a 20 MW SOFC plant is installed on-board to supply hotel loads and assisting three dual-fuel (DF) diesel/LNG generator sets. LNG consumption and emissions are estimated both for the SOFC plant and DF generator sets. It results that the use of LNG-SOFC plant in comparison to DF generator sets allows to limit significantly the SOx, CO, NOx, PM emissions and to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To this extent, the use of HT-PEMFCs could avoid poisoning problems, but HT-PEMFCs still have lower technological maturity with respect to LT-PEMFCs (referred to as PEMFCs) [14]. For this reason, together with the economic convenience and technological maturity of ICE in comparison with PEMFCs, LNG is normally used in ICE, dual-fuel, and sometimes SOFCs, rather than in PEMFCs [101,102]. Lastly, it should be noticed that LNG is a fossil fuel and as such would not be able to guarantee zero-emission shipping.…”
Section: Hydrogen Carriersmentioning
confidence: 99%
“…To this extent, the use of HT-PEMFCs could avoid poisoning problems, but HT-PEMFCs still have lower technological maturity with respect to LT-PEMFCs (referred to as PEMFCs) [14]. For this reason, together with the economic convenience and technological maturity of ICE in comparison with PEMFCs, LNG is normally used in ICE, dual-fuel, and sometimes SOFCs, rather than in PEMFCs [101,102]. Lastly, it should be noticed that LNG is a fossil fuel and as such would not be able to guarantee zero-emission shipping.…”
Section: Hydrogen Carriersmentioning
confidence: 99%
“…Our estimated total wake power was thus ∼3 times lower than expected, indicating either an unaccounted energy loss in the system, or that our methodological approach does not capture all the turbulence in the wake. Part of the losses for the RoPax case could be explained by its comparatively higher hotel load (all energy demanding activities onboard not related to propulsion), which is usually 30-40% of the total engine load, mainly due to passenger-related services (Micoli et al, 2021;Braekken et al, 2023). Consequently, a smaller portion of the installed power will be converted to trust power on a passenger vessel, which is a likely explanation to why the estimated total power was smaller relative the installed power for the RoPax than for the Tanker.…”
Section: Turbulent Wake Intensity and Decaymentioning
confidence: 99%
“…Thus, SOFCs are highly suitable for shipping (Yuan et al, 2020;Pan et al, 2021;Rivarolo et al, 2021). Micoli et al (Luca et al, 2021) reported a 20 MW-class SOFC for a cruise ship. The results showed that the SOFC consumes less natural gas and has cleaner exhaust gas than a dual-fuel engine for the same power.…”
Section: Article Highlightsmentioning
confidence: 99%